(3GdENJUGU ai GdbQGQ GdEOGQi (B: s (3OQGSI ebGQfI (B/ s - (3SejI YHOg gOjgOs; (3LGHQ LGO fUGQ s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2012)
(3JfGhdJ GdQSGdI TQMB eHSWB h SQjYB dJYQja GdbQGQ GdEOGQi h CQcGfg h Qcf GdGNJUGU ajg(B. (3Ke bSeJ GdQSGdI dbSejf ef YOI CHhGH h aUhd h eHGMK h eWGdH JfGhd GdbSe GdChd GdeHGOF GdYGeI dacQI GdGNJUGU h YfGUQ GdGNJUGU h gi GdYfUQ GdTNUi h GdYfUQ GdehVhYi h GdYfUQ GdRefi h GdYfUQ GdecGfi(B. (3CeG GdbSe GdKGfi abO JfGhd QbGHI GdbVGA GdGOGQi dQcf GdGNJUGU ai OYhi GdEdZGA (B((3YjH YOe GdGNJUGU(B) (3h Pdc HHjGf GdCMcGe GdYGeI dgPG GdYjH h UhQI h OQLGJg Ke eHMK NGU Yf fXQjI GfYOGe GdbQGQGJ GdEOGQi h cjajI eMh h RhGd YjH YOe GdGNJUGU Ke eSDhdjI GdEOGQI HGdJYhjV Yf YjH YOe GdGNJUGUs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdYGe, (B2012s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B301-306s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdYGes; (3GdbQGQ GdEOGQis; (3YjH YOe GdGNJUGUs; (3eOdhd GdGNJUGUs; (3efMfjGJ GdYfUQ GdTNUj aj GdGNJUGUs; (3GdYfUQ GdehVhYj hGdRefj aj GdGNJUGUs; (3YOe GdGNJUGU GdSdHj hGdGjLGHjs; (3GdSMH hGdGdZGA GdGOGQjs; (3JUMjM YjH YOe GdGNJUGUs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdYGes